Why Do Village Officials Commit Fraud? Exploring the Underlying Factors - Luh Komang Merawati; Ni Made Sunarsih; Luh Kalpika Jyunda Aryputri Suardyana (Jurnal Inovasi Akuntansi (JIA), 2025)
Fraudulent behavior refers to deliberate deception or misconduct carried out by individuals or groups, aiming to gain unfair advantages at the expense of others. Such actions are typically committed with full awareness of their potential to harm other individuals or entities. This study aims to examine the influence of pressure, opportunity, rationalization, gender, and information asymmetry on the tendency to commit fraud within village governments in Denpasar City. The population in this study consists of all village officials serving as Heads of Section and Heads of Affairs who are directly involved in the administration and financial management of villages, using purposive sample, a total of 46 respondents were obtained within 27 villages. Data analysis was conducted using the Partial Least Squares (PLS) method. The results show that opportunity has a significant positive influence on the tendency to engage in fraudulent behavior among village officials. In other words, the greater the opportunity, the higher the likelihood of committing fraud. In contrast, pressure, rationalization, gender, and information asymmetry do not have a significant impact on fraudulent tendencies in the village governments of Denpasar city.